Pharmacological inhibition of lysine-specific demethylase 1 (LSD1) induces global transcriptional deregulation and ultrastructural alterations that impair viability in Schistosoma mansoni. - Vitor Coutinho Carneiro; Isabel Caetano de Abreu da Silva; Murilo Sena Amaral; Adriana S A Pereira; Gilbert Oliveira Silveira; David da Silva Pires; Sergio Verjovski-Almeida; Frank J Dekker; Dante Rotili; Antonello Mai; Eduardo José Lopes-Torres; Dina Robaa; et al. (Public Library of Science (PLoS), 2020)
Treatment and control of schistosomiasis still rely on only one effective drug, praziquantel (PZQ) and, due to mass treatment, the increasing risk of selecting for schistosome strains that are resistant to PZQ has alerted investigators to the urgent need to develop novel therapeutic strategies. The histone-modifying enzymes (HMEs) represent promising targets for the development of epigenetic drugs against Schistosoma mansoni. In the present study, we targeted the S. mansoni lysine-specific demethylase 1 (SmLSD1), a transcriptional corepressor, using a novel and selective synthetic inhibitor, MC3935, which was used to treat schistosomula and adult worms in vitro. By using cell viability assays and optical and electron microscopy, we showed that treatment with MC3935 affected parasite motility, egg-laying, tegument, and cellular organelle structures, culminating in the death of schistosomula and adult worms. In silico molecular modeling and docking analysis suggested that MC3935 binds to the catalytic pocket of SmLSD1. Western blot analysis revealed that MC3935 inhibited SmLSD1 demethylation activity of H3K4me1/2. Knockdown of SmLSD1 by RNAi recapitulated MC3935 phenotypes in adult worms. RNA-Seq analysis of MC3935-treated parasites revealed significant differences in gene expression related to critical biological processes. Collectively, our findings show that SmLSD1 is a promising drug target for the treatment of schistosomiasis and strongly support the further development and in vivo testing of selective schistosome LSD1 inhibitors.